2001
DOI: 10.1046/j.1440-1819.2001.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Early sexual abuse and low cortisol

Abstract: Post-traumatic stress disorder (PTSD) is a mental health disorder precipitated by a stressful event that produces fear or terror in the individual. Post-traumatic stress disorder studies, particularly in early sexual abuse, have been associated with neuroendocrine dysfunction, most notably the hypothalamic-pituitary-adrenal (HPA) axis. Since the literature on PTSD and neuroendocrine factors in young subjects has been sparse, the present studies were designed to look at the basal functioning of the HPA axis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 20 publications
3
77
2
2
Order By: Relevance
“…As such, it may be an indication of an increase in experienced longer term stress in the DP + group. Interestingly, studies investigating children who had gone through stressful experiences have reported similar results, as this current study with respect to low morning cortisol levels (King et al, 2001;Goenjian et al, 1996). Although none of the subjects in the current study had a PTSD diagnosis, other stress-related factors, like early adverse life events and recent stressful events, that could have an effect on HPA axis functioning were not assessed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As such, it may be an indication of an increase in experienced longer term stress in the DP + group. Interestingly, studies investigating children who had gone through stressful experiences have reported similar results, as this current study with respect to low morning cortisol levels (King et al, 2001;Goenjian et al, 1996). Although none of the subjects in the current study had a PTSD diagnosis, other stress-related factors, like early adverse life events and recent stressful events, that could have an effect on HPA axis functioning were not assessed.…”
Section: Discussionsupporting
confidence: 82%
“…While an association between low cortisol levels and antisocial behavior has consistently been found in adults (Virkkunen, 1985;King et al, 2001;Woodman et al, 1978), findings in children and adolescents are less clear. Some studies in minors demonstrated low cortisol levels in resting conditions to be associated with antisocial behavior (Pajer et al, 2001;McBurnett et al, 2000;Tennes et al, 1986;Tennes and Kreye, 1985), whereas others did not report a significant relationship (Azar et al, 2004;Schulz et al, 1997;Kruesi et al, 1989;Scerbo and Kolko, 1994;Klimes-Dougan et al, 2001;Stoff et al, 1992).…”
Section: Introductionmentioning
confidence: 96%
“…However, in the menopause literature there is evidence consistent with an alternative biologic mechanism, possibly involving underactivity of the HPA axis. (Allsworth et al, 2004;Heim, Ehlert, & Hellhammer, 2000;King, Mandansky, King, Fletcher, & Brewer, 2001;McEwen, 1998) Under the underactivity paradigm, prolonged or severe stress may lead to suppression of the HPA axis, which results in fewer ovulatory cycles and reduced follicle depletion. According to Heim (Heim, Ehlert, Rexhausen, Hanker, & Hellhammer, 1997) and Gunnar, (Gunnar & Vazquez, 2001) underactivity of the HPA axis may be more common than previously understood, especially among individuals exposed to chronic stress.…”
Section: Limitationsmentioning
confidence: 99%
“…Of these, several did not report the time since abuse and so are not discussed here. King, Mandansky, King, Fletcher, and Brewer (2001) identified 10 girls who had experienced CSA in the past month (as reported by parents and/or social service agencies). The group was mostly white (70%), and 5 to 7 years of age.…”
Section: Biological Functioning After Csa Among Childrenmentioning
confidence: 99%